Motivasi Membaca Siswa di Daerah Rural Berdasarkan Jenis Sekolah dan Gender - Nugraha, M Fadli; Dewi, Salamiah Sari; Siregar, Erlina Sari (Universitas Muhammadiyah Metro, 2023)
Recently, no research was found to differentiate reading motivation but focused on reading interest, so this research aimed to look at differences in students' reading motivation based on school type and gender because these two issues are rarely analyzed. Two hypotheses are proposed, namely (H1) There are differences in reading motivation based on gender (H2) There are differences in reading motivation based on school type. Strata took samples and data using a reading motivation scale, which will then be analyzed using a t-test. The results of this study explain that there are no differences in rural students' reading motivation based on gender, meaning that this study rejects the first alternative hypothesis. However, we accept the second alternative hypothesis because it proves differences in reading motivation based on school type. The impacts and recommendations are explained later in this research.